Advanced manufacturing techniques using laser material processing - Akinlabi, Esther Titilayo, 1976-; Mahamood, Rasheedat Modupe, 1973-; Akinlabi, Stephen Akinwale, 1973-; IGI eBooks; IGI Global (Hershey, Pennsylvania (701 E. Chocolate Avenue, Hershey, PA 17033, USA) : IGI Global, 2016)
"This book explores the latest methodologies for using lasers in materials manufacturing and production, the benefits of using lasers in industrial settings, as well as future outlooks for this technology"--Provided by publisher.
Laser additive manufacturing / Rasheedat Modupe Mahamood, Esther Titilayo Akinlabi -- Laser-based manufacturing processes for aerospace applications / Panos Stavropoulos, Angelos Koutsomichalis, Nikos Vaxevanidis -- Laser metal deposition process / Rasheedat M. Mahamood -- Enhancement of surface integrity of titanium alloy with copper by means of laser metal deposition process / Mutiu F. Erinosho, Esther T. Akinlabi, Sisa Pityana -- Trend and development in laser surface modification for enhanced materials properties / Muhammed Olawale Hakeem Amuda, Esther Titilayo Akinlabi -- Laser surface processing for tailoring of properties by optimization of microstructure / Jyotsna Dutta Majumdar, Andreas Weisheit, I. Manna -- Mitigation of wear damage by laser surface alloying technique / Isaac Damilola Adebiyi, Patricia A. P. Popoola, Sisa Pityana -- Computational dynamics of laser alloyed metallic materials for improved corrosion performance: computational dynamics of laser alloyed metallic materials / Olawale Samuel Fatoba [and 3 others] -- Laser additive manufacturing of titanium-based implants: a review / Martin Ruthandi Maina.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed 04/21/2016).
Keywords: Manufacturing processes; Lasers -- Industrial applications; Solid freeform fabrication; Thin films; Surface preparation; Computer-aided design (CAD); Laser additive manufacturing; Laser machining; Laser metal deposition; Laser surface alloying; Laser surface modification; Laser-material interaction; Process optimization; Electronic books